Penerapan Bimbingan Konseling Kelompok untuk Meningkatkan Sopan Santun pada Siswa Kelas X Di SMK X - Indah Restari, Putri; Laily, Nadhirotul (Jurnal Ilmiah Psyche, 2025)
This study aims to determine the effectiveness of group counseling services in improving students’ politeness at Vocational High School (SMK) X. This research employed a quantitative approach with a pre-experimental design (One-Group Pretest–Posttest Design). The research subjects consisted of 17 students who had low levels of politeness based on the pretest results. The instrument used was the Politeness Scale by Dahraini (2020), which has a reliability value of 0.856. Data analysis using the Wilcoxon test showed a significance value of 0.001 (< 0.05), indicating a significant difference between the scores before and after the treatment. The N-Gain score of 0.59 indicates an improvement in the moderate category. The results of this study demonstrate that group counseling services using the problem-solving technique are effective in fostering students’ moral awareness, empathy, and polite behavior within the school environment.